Sorption of the Simplest Carboxylic Acids on Clay-Like Mineral Glauconite: Reduction of Integral Toxicity of Aqueous Solutions - Tsygankova, L.E. (Journal of Applied Solution Chemistry and Modeling, 2018)
The integral toxicity of solutions of a number of carboxylic acids was estimated by measuring their chemical oxygen consumption (COC) and the biochemical oxygen demand for the biodegradation of substances due to microorganisms (BOD5). The analytical dependences of COC and BOD5 as well as of their ratio for these compounds on concentration were determined. The values of COC and BOD5 for a number of acid solution mixtures were measured. The coefficient that indicates biodegradability of substances has been calculated. The chemical consumption of oxygen by solutions of organic acids is shown to increase with the transition from lower to higher homologues and with increase in the concentration of the solution. The kinetics and degree of removal of organic acids out of solutions due to sorption on the clay-like mineral, glauconite, have been studied. Glauconite that is the natural sorbent is characterized by a high adsorbing power in solutions of organic acids under both stationary and non-stationary conditions. However, adsorption becomes complicated as complexity of the organic acid molecule structure grows. To achieve more comprehensive removal of acids out of solutions, one reduces flow rate and increases thickness of the sorbent layer.